Arctic transshipment hub planning along the Northern Sea Route : A systematic literature review and policy implications of Arctic port infrastructure - Hermann, Roberto Rivas; Lin, Ning; Lebel, Julien; Kovalenko, Alina (Marine Policy, 2022)
publishedVersion